2017
DOI: 10.1192/bjp.bp.115.180653
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol as a predictor of psychological therapy response in depressive disorders: Systematic review and meta-analysis

Abstract: Our findings suggest that patients with depression with elevated HPA functioning are less responsive to psychological therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 27 publications
4
45
1
3
Order By: Relevance
“…This indicates that basal cortisol level is unlikely to be influenced by ICBT intervention. This was supported by findings of a recent systematic review and meta-analysis that investigated if cortisol level could be a predictor of treatment response to psychological therapy in depression [33]. However, because of the limited sample size, our findings should be considered as preliminary.…”
Section: Discussionsupporting
confidence: 82%
“…This indicates that basal cortisol level is unlikely to be influenced by ICBT intervention. This was supported by findings of a recent systematic review and meta-analysis that investigated if cortisol level could be a predictor of treatment response to psychological therapy in depression [33]. However, because of the limited sample size, our findings should be considered as preliminary.…”
Section: Discussionsupporting
confidence: 82%
“…This is supported by a recent review of chronic cortisol levels measured in hair, supporting the hypothesis of cortisol hyperactivity in depression but hypoactivity in other illnesses such as panic disorder 106. Furthermore, particularly, elevated cortisol levels may predict a poorer response to psychological107 and antidepressant108 treatment. Historically, the most promising neuroendocrine marker of prospective treatment response has been the dexamethasone suppression test, where cortisol nonsuppression following dexamethasone administration is associated with a lower likelihood of subsequent remission.…”
Section: Introductionmentioning
confidence: 66%
“…Stetler et al (2011), for example, found that higher cortisol levels were evident with a moderate effect size in MDD using meta-analysis. Prior studies of cortisol as a predictor of MDD treatment with psychological (Fischer et al, 2017) and antidepressant treatment (Kin et al, 1997) have suggested that higher levels are a poor prognostic sign. To our knowledge, this is the first report to suggest that lower cortisol in older adults might be diagnostic and a poor prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the immense and growing cost of Major Depressive Disorder (MDD) to individuals (Ferrari et al, 2013) and society (Greenberg et al, 2015), uncovering physiological biomarkers associated with depression that may predict treatment response is of high importance. Data accumulated over four decades of research indicate that the hypothalamicpituitary-adrenal (HPA) axis plays a key role in the pathophysiology of MDD (Stetler and Miller, 2011;Wolkowitz et al, 2009) and might have utility for prediction of depression symptom outcome to psychological treatments (Fischer et al, 2017). However, inconsistent results in the relationship between HPA axis markers such as cortisol and MDD suggest the presence of moderators such as age (Stetler and Miller, 2011).…”
Section: Introductionmentioning
confidence: 99%